The Competency of Administrative Court in Adjudicating State Financial Losses Report Dispute in Indonesia - Helmi Helmi; Fauzi Syam; Harry Setya Nugraha; Retno Kusniati (Faculty of Law, Sriwijaya University, Indonesia, 2020)
The debate on the absolute competency of the State Administrative Court in Indonesia to set the dispute over the State Financial Losses Report (LHPKKN) is proved to have caused dissenting opinion. The judgments between one administrative court to other court in Indonesia cause main problem of achieving justice and legal certainty. This research examines the issue of absolute competence of the Administrative Court in adjudicating disputes on the State Financial Losses Report published by the Financial and Development Monitoring Agency (BPKP). This article uses normative legal research and implement the statute approach, conceptual approach, and case approach. These approaches are used to discern and analyze several related legal materials or documents scientifically. The aims and objectives of this research are to find a legal solution on how this classic issue has to be approached and solved. As a result, it is found through this article that the Administrative Court has absolute competence in deciding disputes on the Report on the Calculation of State Financial Losses issued by the Financial and Development Monitoring Agency, which is supported by several fundamental reasons.